Instagram Content Engagement in Islamic Philanthropy: Evidence from BAZNAS Indonesia - Lusi Emawati; M Fahmi Hidayat; Rulli Kurniawan; Eneng Riska Rahayu Putri (Ijtimā'iyya Journal of Muslim Society Research, 2026)
This study examines how Instagram content characteristics shape audience engagement in Islamic philanthropy, using BAZNAS Indonesia as a case. A quantitative content analysis was conducted on 544 organic posts published by @baznasindonesia from January to May 2025. Post type, publication timing, message interactivity, and post appeal were manually coded, and Ordinary Least Squares (OLS) models were estimated for log-transformed likes and comments. Entertainment appeal significantly increased likes (β = 1.451, p = 0.015) and comments (β = 2.176, p = 0.002). Posts published on public holidays received more likes (β = 0.441, p = 0.004), whereas images (β = −0.277, p = 0.015) and Reels (β = −0.510, p < 0.001) generated fewer likes than carousels. Message interactivity was not significant for either likes (p = 0.388) or comments (p = 0.365). The study contributes to Islamic communication and digital-philanthropy scholarship by showing that engagement is shaped not simply by calls to action, but by the interaction between format, timing, and ethically framed edutainment. It proposes a sharia-based edutainment strategy that combines attention-generating content with truthful, educational, dignified, and non-exploitative communication.